2013
DOI: 10.1155/2013/964070
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Is Not as Effective as Physical Exercise for Improving Reproductive and Metabolic Functions in Rats with Dihydrotestosterone-Induced Polycystic Ovary Syndrome

Abstract: Polycystic ovary syndrome (PCOS) is a reproductive and metabolic disorder associated with obesity and insulin resistance that often precedes the development of type-2 diabetes. Rats continuously exposed to dihydrotestosterone from prepuberty display typical reproductive and metabolic PCOS characteristics including anovulation, polycystic ovaries, insulin resistance, and obesity. Our aim was to investigate if resveratrol improves reproductive and metabolic functions in PCOS rats. The effect was compared to exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 57 publications
(95 reference statements)
4
27
0
Order By: Relevance
“…CYP11A1, located in the mitochondria and regulating the first step in steroidogenesis, was likely down-regulated in DHT-exposed mice due to negative feedback. This is in line with data from DHT-induced rats (20) and supports the hypothesis that mitochondrial function is impaired in PCOS (55). As judged by the absence of DHT-induced changes in Cyp19a1 and Hsd3b gene expression in APNtg mice, our data suggest adiponectin has a small protective effect on ovarian function in DHT-induced mice with PCOS-like traits.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…CYP11A1, located in the mitochondria and regulating the first step in steroidogenesis, was likely down-regulated in DHT-exposed mice due to negative feedback. This is in line with data from DHT-induced rats (20) and supports the hypothesis that mitochondrial function is impaired in PCOS (55). As judged by the absence of DHT-induced changes in Cyp19a1 and Hsd3b gene expression in APNtg mice, our data suggest adiponectin has a small protective effect on ovarian function in DHT-induced mice with PCOS-like traits.…”
Section: Discussionsupporting
confidence: 92%
“…We have shown that adiponectin receptors 1 and 2 are increased in ovaries in PCOS rat models (19,20), and accumulating evidence suggests a direct role for adiponectin in female reproductive tissues (18). Moreover, a lower proportion of theca cells express adiponectin receptors in polycystic ovaries compared with normal ovaries (21).…”
mentioning
confidence: 92%
“…Likewise, it has been demonstrated that resveratrol promotes apoptosis (34) and decreases vascular permeability (53) in cultures of ovarian theca cells, which are the major site of androgen synthesis. Therefore, our results extend those findings to show that this polyphenol reduces androgen levels in vitro (35,54), whereas conversely resveratrol treatment did not seem to exert the same effect in another in vivo study (48). These different results may be due to experimental animal PCOS model used in such research, in which it was not possible to achieve an improvement of insulin sensitivity after resveratrol treatment; thus this finding supports that resveratrol might act on androgens levels via insulinsensitizing effects.…”
Section: Discussionsupporting
confidence: 77%
“…These properties of resveratrol were observed at a lower dose and shorter treatment period than in other studies that have reported similar effects in different animal models of obesity (38,47). In a previous study using PCOS animal models, which are usually associated with increased insulin resistance, treatment with higher doses of resveratrol administered for a longer period did not improve insulin sensitivity (48). However, in that study the dihydrotestosterone-induced rat PCOS model was used, and the mechanisms underlying insulin resistance in these animals, such as proinflammatory state, may be different from those in leptin-deficient obese mice.…”
Section: Discussionsupporting
confidence: 72%
“…Finally, consistent with our results, several studies have shown that resveratrol supplementation significantly improved insulin sensitivity in PCOS patients. The mechanism underlying the beneficial effect of resveratrol on glucose control may involve the following aspects: resveratrol can activate the in vivo expression of sirtuin 1 (28,29), which acts downstream of energy restriction and provides a beneficial effect on glucose control (30); resveratrol can stimulate glucose uptake by increasing the expression of GLUT4, which is the insulindependent glucose transporter (30); resveratrol is able to activate glucose uptake in the absence of insulin. Additionally, the liquid like nature and reduced size of the particles of inorganic-resveratrol (revifast®) offer an improved bioavailability of resveratrol and other advantages, such as stability, flowability and compressibility (17).…”
Section: @ C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%